2022
DOI: 10.1007/s11694-021-01275-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polysaccharide-based coatings on postharvest storage life of grape: measuring the changes in nutritional, antioxidant and phenolic compounds

Abstract: In this study, the effect of postharvest coating of chitosan (CH) 1.0%, gum ghatti (GG) 1.0% and combine of each other, on nutritional properties, phenolic compounds and antioxidant capacity of ‘Rishbaba’ grape ( Vitis vinifera L.) was evaluated during 60 days of cold storage. Coating with 1.0% CH solely or in combined with 1.0% GG caused a considerable retain in grape berries phenolic acids compared to uncounted samples after the 60th day. Moreover, flavanols and flavan-3-ols content we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
3
16
1
Order By: Relevance
“…Our results corroborate the findings of Baraiya et al (2016) who recommended the application of xanthan gum edible coating to improve the consumer preference of table grapes. In a similar finding, Eshghi et al (2022) also reported that the polysaccharide and "gum ghatti" edible coating improved the overall fruit quality of grapes.…”
Section: Consumer Preferencesupporting
confidence: 53%
See 3 more Smart Citations
“…Our results corroborate the findings of Baraiya et al (2016) who recommended the application of xanthan gum edible coating to improve the consumer preference of table grapes. In a similar finding, Eshghi et al (2022) also reported that the polysaccharide and "gum ghatti" edible coating improved the overall fruit quality of grapes.…”
Section: Consumer Preferencesupporting
confidence: 53%
“…Control Gum Arabic (10%) Guar gum (1.5%) CMC (1%) Xanthan gum (0.3%) polysaccharide ability for retaining the nutritional components of fruit (Eshghi et al, 2022).…”
Section: Storage Period (Days)mentioning
confidence: 99%
See 2 more Smart Citations
“…Sample preparation for mold and yeast counts was achieved in aseptic conditions (laminar flow, gloves, and scalpels), for each replicate, based on the method described by Jafari et al (2021) [ 68 ] and Eshghi et al (2022) [ 69 ]. Briefly, 10 g of sample was mixed with 90 mL of sterilized distilled water in 100 mL Erlenmeyer flask.…”
Section: Methodsmentioning
confidence: 99%